Instâncias da representação imagética hiper-real - Silva, Eduardo Pinto da (2012)
The approach that undertakes this work revolves around the emergence of iconic structures on reflecting about the meaning of different methods of image representation through which the contemporaneity reveals itself. At baseline, three aspects are considered looking for an analytical ontology of the act of representation and imagery: the transition of representation in the oral culture of societies for writing, from these to typography, and finally the creation of a representation device. Resorted to, therefore, the argument by some genealogy reference points that technological instances such as writing, printing and photography, the evolution of this process, correspond, in itself, a consequent shift technique, for each representation precedent. In the area of the image, the most salient aspect of this change in foward process is the emergence of hyper-reality: the instances of hyper-realistic representation. In the Western context, the 'simulation of the world' - essential idea of mimesis is the work of an autonomous an conventional system. It should be noted, then the fact that under unreflective of the post-industrial societies, the mass-media image is coating with natural or fake code including - according to Baudrillard - tends to replace the real world in the "perpetuation of a large chain of simulacra." Hence in modern times, in the postindustrial society, during the crisis of the representation regimen and perception, centered in the referent. In this limit, new settings are established by aesthetic representations of imagery in contemporary culture: establishing spaces of simulation [Jean Baudrillard] the spectacle [Guy Debord] and hypermodernity [Gilles Lipovetsky] in which they operate. In these assemblages, saps the emergence of Hyper-reality Representation Instances - as seen in this study aesthetic events to configure itineraries of a new sensibility. It is the nature of this practice sign-iconic, ingrained in the creation of current artistic expression, which this research engaged in peering: the hyper-realistic setting, taking empirical support central to contemporary imagery production, diverse formats of analog representation.